2020
DOI: 10.1016/j.dsx.2020.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy did not improve the in-hospital outcome of coronavirus disease 2019 (COVID-19) infection

Abstract: Background and aims The coronavirus disease 2019 (COVID-19) number of death cases is still increasing. One of the comorbidities associated with severe outcome and mortality of COVID-19 is dyslipidemia. Statin is one of the drugs which is most commonly used for the treatment of dyslipidemic patients. This study aims to analyze the association between statin use and in-hospital outcomes of COVID-19 infection. Methods We systematically searched the Google Scholar database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 14 publications
1
93
2
2
Order By: Relevance
“…In fact, the results using adjusted data confirm those reported in the meta-analysis by Kow et al [12] , who reported a 30% reduction in fatal or severe COVID-19 infection. On the other hand, the univariate analyses confirm the lack of significant protection among statin users reported in the meta-analysis by Hariyanto et al [13] .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In fact, the results using adjusted data confirm those reported in the meta-analysis by Kow et al [12] , who reported a 30% reduction in fatal or severe COVID-19 infection. On the other hand, the univariate analyses confirm the lack of significant protection among statin users reported in the meta-analysis by Hariyanto et al [13] .…”
Section: Discussionsupporting
confidence: 81%
“…Any resulting discrepancies were resolved by mutual discussion. The reference lists of previous systematic reviews and meta-analyses [12] , [13] and of any related narrative reviews or commentaries [16] , especially those involving diabetes populations [3] , [4] , were manually examined to identify any additional publications relevant to the present study. A search for duplicates was done manually.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results on statin use and its potential benefits for COVID-19 patients are controversial. In a recent meta-analysis, it was reported that “statin use did not improve in-hospital outcomes of COVID-19 infections” [ 39 ]; this analysis included 9 studies with a total of 3449 patients. The results showed that statin use did not improve the outcome severity [OR = 1.64, 95% CI: (0.51–5.23), P = 0.41, I2 = 93%, random-effect modelling] or the mortality rate associated with COVID-19 infection [OR 0.78, 95% CI: (0.50–1.21), p = 0.26, I2 = 0%, fixed-effect modelling] [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This abrupt onset of disease progression has contributed to an increase in the mortality rate of the disease. Several comorbidities have also been demonstrated to be associated with the development of severe COVID-19, such as hypertension, diabetes mellitus, dyslipidemia, thyroid disease, cardiovascular disease, dementia, and pulmonary disease [ [6] , [7] , [8] , [9] ]. Therefore, prompt identification and containment, which are achievable through strict surveillance and early diagnosis, are very important.…”
Section: Introductionmentioning
confidence: 99%